The Mirror of the Infinite: Gregory of Nyssa on the Vestigia Trinitatis - Hart, David Bentley (Modern theology, 2002)
This essay attempts to demonstrate something of the subtlety and complexity of Gregory of Nyssa’s Trinitarian theology by paying close attention to the way in which, for Gregory, the Triune God is reflected in the "mirror" of the soul—both in its creaturely constitution and in the process of its sanctification by the Holy Spirit. The article is intended chiefly as an argument against the fashionable scholarly opposition between "Eastern" and "Western"—or "Cappadocian" and "Augustinian"—Trinitarianisms; it also is intended as an argument against "social" and "psychological" models of the Trinity alike (neither of which enjoys patristic warrant).